Q-methodology and farmers' decision-making - van Dijk, Ruben; Intriago Zambrano, Juan Carlo; Diehl, Jan Carel; Ertsen, Maurits W. (Frontiers in Sustainable Food Systems, 2022)
Despite extensive research on farmers’ constraints and decisions, technology developers, policymakers and development organizations still encounter difficulties in relating policies to farmers’ strategies. Often, the concept of ‘smallholders’ is applied as explaining and predicting farmers’ decisions – suggesting that specific strategies of farmers can be meaningfully related to their farm size. Our study into farmers’ decision-making concerning water transport technologies in Malawi suggests that this way of grouping farmers in policy and development programs does not match actual decision strategies. Using Q-methodology (Q) as a method allowed us to find decision-making patterns without predefining variables that would influence decision-making. We found that farmers within a predefined smallholder group did not decide in the same ways. Furthermore, our results show that decision-making has a clear gender dimension. We argue that Q is able to capture the nuances of farmers’ decision-making processes. As such, the methodology potentially provides a useful feed for policy and technology development.